2014
DOI: 10.2139/ssrn.2523383
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Model-Based Regulation

Abstract: In this paper, we investigate how the introduction of complex, model-based capital regulation affected credit risk of financial institutions. Model-based regulation was meant to enhance the stability of the financial sector by making capital charges more sensitive to risk. Exploiting the staggered introduction of the model-based approach in Germany and the richness of our loan-level data set, we show that (1) internal risk estimates employed for regulatory purposes systematically underpredict actual default ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
86
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 35 publications
(30 reference statements)
14
86
0
Order By: Relevance
“…While providing increasing incentives for prudent in-house risk management over time, regulators effectively also tolerated carve-outs of bank equity, and thus a serious decline in resiliency, particularly for the large and systemically most important banks after 2005. This is consistent with the view that risk models were chosen strategically (see Behn, Haselmann and Vig (2014) and Colliard (2015), but also Admati and Hellwig (2013).) Ironically, these carve-outs were one way of increasing return on equity through extensive stock repurchases at a time, when the cost of bank equity was actually low, and strengthening capitalization and resiliency was relatively cheap (in historical context).…”
Section: Unintended Consequencessupporting
confidence: 86%
“…While providing increasing incentives for prudent in-house risk management over time, regulators effectively also tolerated carve-outs of bank equity, and thus a serious decline in resiliency, particularly for the large and systemically most important banks after 2005. This is consistent with the view that risk models were chosen strategically (see Behn, Haselmann and Vig (2014) and Colliard (2015), but also Admati and Hellwig (2013).) Ironically, these carve-outs were one way of increasing return on equity through extensive stock repurchases at a time, when the cost of bank equity was actually low, and strengthening capitalization and resiliency was relatively cheap (in historical context).…”
Section: Unintended Consequencessupporting
confidence: 86%
“…Finally, concerning internal credit risk models we confirm and extend the re-sults of Behn, Haselmann and Vig (2014) about the limitations of model-based regulation. Also they find negative effects of internal models for credit risk on the resiliency of German banks.…”
supporting
confidence: 78%
“…To quantify these parameters, the regulator must be able to evaluate the risks of the bank's investments. However, the 2008-2009 financial crisis revealed that risk modeling in the financial sector has strong limits (e.g., Danielsson (2002), Danielsson (2008), Hellwig (2010), Behn, Haselmann, and Vig (2014), and Rajan, Seru, and Vig (2015)). …”
Section: Regulating Compensation Schemesmentioning
confidence: 99%
“…However, the 2008-2009 financial crisis revealed that measuring bank asset risk is a difficult task because risk modeling per se has strong limitations (Danielsson, 2002(Danielsson, , 2008Hellwig, 2010;Rajan, Seru, and Vig, 2015). In addition, with risk-weighted capital requirements, banks have an incentive to understate their asset risk (Behn, Haselmann, and Vig, 2014) and to engage in regulatory capital arbitrage (e.g., Cochrane, 2014).…”
Section: Introductionmentioning
confidence: 99%